(DIS)JOINING (DIS)JUNCTURE - Rawoot, Maashitoh (School of Architecture, Planning and Geomatics, 2017)
This project began with an encounter with a place, an ambivalent place of disjunction between a mountain and a wasteland in the city. The subsequent uncovering of untold stories, traces of memory, about that place, reveal a site laden with a history of a deep connection between a people and their natural surroundings. Ensuing events of disjunction and displacement has indented into it layers, which has left it a severed site of strange contradictions. This paper explores the fragmented nature of the memory of a place; that it cannot simply be recreated, and in fact should not be. Rather, the dissertation research looks at ways in which art and architecture are manipulated to disrupt the way think we perceive a place and reframe our presumptions, such that latent layers of an existing place can be awakened and brought into presence in a new way. The project departs from the position that the disjunctions of a place can in fact be the site of shifting perceptions and unexpected connection, as is asserted by Stuart Hall in "Maps of Emergency: Fault Lines and Tectonic Plates": ..."Of course, fault lines… are also productive. Those escaping the vertical lines of force forge new lateral connections. New formations appear where older ones disappear beneath the sand. Borders, which divide, become sites of surreptitious crossing. Separate and inviolable worlds meet and collide. Where only the pure, the orthodox, were valorised, a new universe of vernaculars and creole forms comes into existence." This particular design process was one of actively harnessing all the layers of the site, past and present, strange and ordinary, connections and disjunctions, to bring about a new, shifted experience of the place.